Attitudes of Physical Education Teachers towards Their Work as a Precondition of Their Professional Position - Trinkūnienė, Laima (Pedagogika, 2015)
The aim of the present research was to reveal the attitudes of physical education teachers towards their work as a precondition of their professional position. Independent sample consisted of 324 Lithuanian physical education teachers (183 men and 141 women, or 56.6 per cent and 43.5 percent). Teachers’ attitudes towards their work were revealed using a 14-point scale developed on the basis of V. Gerikienė (2007) questionnaire. It was established that both male and female teachers did not demonstrate high levels of affective identity (organizational pride where they work, happiness to take a certain position) with their organization. The work of physical education teacher was slightly more interesting to women (p < 0.07). Both men and women did not intend to change profession and go to work abroad. Younger physical education teachers more emotionally identified with their schools and they more supported the idea that work at school should be based on trust and responsibility. Women with a teaching experience of less than 20 years, more than their male colleagues with the same experience, were proud of their schools and paid more attention to their professional development, besides they would much more recommend this profession for their children. Physical education teachers (men and women) had no communication problems with their pupils.